Application of Carrageenan, Xanthangum as Biodegradable Coating on Storage of Cherry Tomatoes (Lycopersicon Esculentum) - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2018)
Cherry tomatoes (Lycopersicon esculentum) have been popularly consumed as functional food by their antioxidants as well as good apperance with bright red color and delicious flavor. But cherry tomatoes are prone to desiccation shrinkage and fruit softening during storage, resulting in the decrease of their commodity value. The major postharvest losses of tomatoes are due to fungal infection, physiological disorders, and physical injuries.  The prevalent method of preservation of postharvest cherry tomatoes is the use of moderately low temperatures and high humidity. However, low temperatures induce chilling injury. Application of edible coating on tomatoes is able to reduce quality changes and slow down moisture loss by controlling and modifying the internal atmosphere of the individual fruits. The great benefit conferred by edible coatings is that these are natural biodegradable products. An investigation on coating of cherry tomatoes by using carrageenan and xanthan gum was investigated. Cherry tomatoes which were coated with 0.75% carrageenan still maintained good quality until 30 days of preservation.Keywords: Cherry tomates, Carrageenan, Xanthangum, Biodegradable, Coating, Storage, Shelf-life.